The Ethics of Sharing Hadith on Social Media and Its Impact on Muslim Communities in The Digital Age - Wahid, Abdul; Azmiadi (El-Sunan: Journal of Hadith and Religious Studies, 2025)
The dissemination of hadith through social media has become an inseparable aspect of contemporary religious life in the digital era. While this phenomenon expands the reach of da‘wah and enhances public access to Islamic teachings, it simultaneously generates serious challenges related to the authenticity, validity, and ethical transmission of prophetic traditions. This study aims to analyze the ethical dimensions of sharing hadith on social media and its implications for religious literacy among Muslim communities. Employing a qualitative library-based research design complemented by illustrative content analysis of selected social media posts, this study examines patterns of dissemination, verification practices, and public reception of hadith-based content. The findings indicate that although social media contributes to increasing interest in hadith studies, it also facilitates the widespread circulation of weak and fabricated traditions due to low levels of takhrīj literacy and critical digital awareness. The study further demonstrates that ethical principles such as honesty (ṣidq), verification (tabayyun), and scholarly responsibility are frequently neglected in digital religious practices. This research contributes by offering an integrative framework that connects classical hadith ethics with contemporary digital communication challenges and proposes institutional strategies to strengthen digital religious literacy and responsible da‘wah practices in the public sphere.